Long-standing overt ventriculomegaly in adults (LOVA) as a distinct entity on the neurologist’s differential: a narrative review - Racheed Mani; Jade Basem; Michael Egnor; Guy Schwartz (BMJ Neurology Open)
Long-standing overt ventriculomegaly in adults (LOVA) has been posited as a form of progressive hydrocephalus, with similar clinical and radiographic features to normal pressure hydrocephalus (NPH), but which should be understood as a distinct clinical entity. We conducted a narrative review analysing the literature into LOVA as a distinct form of hydrocephalus with its own clinical and radiographic characteristics and treatment modalities. LOVA is characterised by triventriculomegaly, an Evans’ index of ≥0.4, presenting with progressive symptoms of elevated intracranial pressure after an initial arrest in childhood and head circumferences≥2 SD above the mean. Endoscopic third ventriculostomy is considered the first-line treatment. Shunting is equally effective but confers a higher complication risk profile. LOVA represents a progressive form of hydrocephalus with certain clinical and radiographic features which overlap with NPH, but is a distinct entity which should be on the neurologist’s differential.